Diversity and Distribution of Gastropode (Molusca) in the Mangrove Ecosystem of Apar Village, Pariaman City, West Sumatera Province - Desmarina, Yuyun; Zulkifli, Zulkifli; Nasution, Syafruddin (Journal of Coastal and Ocean Sciences, 2022)
This research was conducted in August 2021 in Apar Village, Pariaman City, West Sumatra Province. This study aims to determine the diversity and distribution pattern of gastropods in the mangrove ecosystem of Apar Village, Pariaman City. The method used in this research is a survey method. A sampling of gastropods was carried out by purposive sampling method and sediment sampling was carried out using a 10 cm paralon pipe with a depth of 10 cm. The results showed that the diversity of gastropods in the waters of Apar Village was included in the low category. The highest density of gastropods was Faunus ater which was found at each station, while the lowest density was Ellobium aurisjudae and Latirolagena smaragdulus which were only found on the coast of Apar Village, Pariaman City. The overall distribution pattern of gastropods at each station was evenly distributed and gastropods in the study area were in the high category. Based on the analysis of sediment organic matter in Apar Village, the highest average value was 29.43% and the lowest was 6.51%. The results of the analysis of the sediment fraction at each station of the sediment type were muddy sand